The Role of Future Time Perspective on Academic Grit Among Engineering Students in Indonesia - Alya Sabrina; Angeline Hosana Zefany Tarigan (Psychology Journal of Mental Health, 2025)
The purpose of this study is to examine the role of Future Time Perspective (FTP) in Academic Grit among engineering students in Indonesia. The hypothesis proposed that FTP significantly contributes to the development of Academic Grit. The participants consisted of 250 active engineering students from various major islands across Indonesia, selected using purposive sampling. The instruments employed were the Academic Grit Scale, developed by the researcher based on aspects from Clark and Malecki (2019), and the Future Time Perspective Scale, also developed by the researcher using aspects from Husman and Shell (2008). Data were analyzed using simple regression analysis. The results revealed an R-square value of 0.436, an F value of 5.531, and a significance level of 0.000 (p < 0.005). These findings indicate that Future Time Perspective has a significant role in Academic Grit, contributing 43.6% to its variance. Therefore, the research hypothesis is accepted.